The Loan Project in Thailand an analysis of its vocational education activities and evaluation of its accomplishments - Tepaya, Witya 1937- (s.n.], 1969)
This study analyzed the Loan Project in Thailand as an education strategy. Content analysis of pertinent documents pertaining to the Loan Project were the primary sources of information. Findings show that the Loan Project is able to fulfill its objectives.